(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
Menstrual abnormalities are common in women nowadays due to lifestyle modifications, changes in dietary habits and lack of excercise. Of these menstrual disorders, amenorrhoea or absence of menstruation is a common clinical presentation for abnormalities of hypothalamo pituitory ovarian axis. Ayurvedic treatise, Vaidya Manorama and Chikitsamanjary mentions the use of root of Amleeka in treating Nastarthava (Amenorrhoea) – which is absence or abnormal cessation of menstruation. Amenorrhoea causes much physical and psychological problems to affected women. Considering the disease scenario, drawbacks of existing treatment modalities in modern medicine (which advocates greater use of steroids, hormones or surgery), effectiveness of the drug used by traditional practitioners and its easy availability, it seems ideal to investigate the effect of root of Amleeka in Nashtartava so as to provide a safe and affordable treatment. The clinical trial was undertaken as a before and after trial with 30 patients for a period of 3 months with the test drug and three months follow up. The assessment criteria were the amount and duration of menstrual bleeding, interval of menstrual cycle and associated symptoms before trial, after trial and after follow up. The trial drug was found to be effective in improving amount of menstrual bleeding from scanty to moderate and duration of bleeding from short to moderate level (P<0.001***). Thus it can be concluded that study drug is effective in inducing menstruation.